TECHNOSCIENCE AS NEW STAGE IN THE DEVELOPMENT OF MODERN SCIENCE AND TECHNOLOGY - Vitalii G. Gorokhov (Высшее образование в России)
The article considers a new phenomenon of the modern science and technology- technoscience. Technoscience is a combination of the natural scientific theory and engineering theory. This is also a new way of the communication between science and society and between science and politics. The article analyzesinterdisciplinarity of technoscience and the role of the theoretical investigation in technoscience. Representative example of technoscience is nanotechnoscience.